Deficiency in Silicon Transporter Lsi1 Compromises Inducibility of Anti-herbivore Defense in Rice Plants - Lin, Yibin; Sun, Zhongxiang; Li, Zhenfang; Xue, Rongrong; Cui, Weikang; Sun, Shaozhi; Liu, Tingting; Zeng, Rensen; Song, Yuanyuan (Frontiers in Plant Science, 2019)
Silicon (Si) application can significantly enhance rice resistance against herbivorous insects. However, the underlying mechanism is elusive. In this study, silicon transporter mutant OsLsi1 and corresponding wild-type rice (WT) were treated with and without Si to determine Si effects on rice resistance to leaffolder (LF), Cnaphalocrocis medinalis (Guenée) (Lepidoptera: Pyralidae). Si application on WT plants significantly promoted rice plant growth, upregulated expression level of OsLsi1 and increased Si accumulation in the leaves and roots, as well as effectively reduced LF weight gain, while it showed only marginal or no effect on the mutant plants. Furthermore, upon LF infestation, transcript levels of OsLOX, OsAOS2, OsCOI1a, OsCOI1b and OsBBPI, and activity of catalase, superoxide dismutase, peroxidase and polyphenol oxidase were significantly higher in Si-treated than untreated WT plants. However, OsLsi1 mutant plants displayed higher susceptibility to LF, and minimal response of defense-related enzymes and jasmonate dependent genes to Si application. These results suggest that induced defense plays a vital role in Si-enhanced resistance and deficiency in silicon transporter Lsi1 compromises inducibility of anti-herbivore defense in rice plants.